The political impact of the Sustainable Development Goals : transforming governance through global goals? - Biermann, Frank, 1967-; Hickmann, Thomas; Sénit, Carole-Anne (Cambridge : Cambridge University Press, 2022)
Written by an international team of over sixty experts and drawing on over three thousand scientific studies, this is the first comprehensive global assessment of the political impact of the Sustainable Development Goals, which were launched by the United Nations in 2015. It explores in detail the political steering effects of the Sustainable Development Goals on the UN system and the policies of countries in the Global North and Global South; on institutional integration and policy coherence; and on the ecological integrity and inclusiveness of sustainability policies worldwide. This book is a key resource for scholars, policymakers and activists concerned with the implementation of the Sustainable Development Goals, and those working in political science, international relations and environmental studies. It is one of a series of publications associated with the Earth System Governance Project. For more publications, see www.cambridge.org/earth-system-governance. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 25 Jul 2022).
Keywords: Sustainable Development Goals; Sustainable development -- Political aspects; World politics